Assessing the impact of oral health disease on quality of life in Ecuador: a mixed-methods study - Krishnan, Nupur; Manresa-Cumarin, Karem; Klabak, Jessica; Krupa, Greg; Gudsoorkar, Priyanka (Frontiers in Oral Health, 2024)
Introduction Globally, oral health diseases surpass all other non-communicable diseases in prevalence; however, they are not well studied in underserved regions, where accessibility to dental services and oral health education is disparately worse. In Ecuador, further research is needed to understand such disparities better. We aimed to assess the effect of oral health disease on individuals' quality of life and how social disparities and cultural beliefs shape this. Methods Individuals 18 or older receiving care at mobile or worksite clinics from May to October 2023 were included. A mixed-methods approach was employed, involving semi-structured interviews, Oral Health-Related Quality of Life (OHRQoL) measures, and extra-oral photographs (EOP). Results The sample (n = 528) included mostly females (56.25%) with a mean age of 34.4 ± 9.44. Most participants (88.26%) reported brushing at least twice daily, and less than 5% reported flossing at least once per day. The median OHRQoL score was 4 (min-max), significantly higher among individuals ≥40 years old, holding high school degrees, or not brushing or flossing regularly (p < 0.05). Identified barriers to good oral health included affordability, time, and forgetfulness. Participants not receiving care with a consistent provider reported fear as an additional barrier. Participants receiving worksite dental services reported these barriers to be alleviated. Dental providers were the primary source of oral hygiene education. Most participants reported oral health concerns, most commonly pain, decay, dysphagia, and halitosis - consistent with EOP analysis. Discussion Findings underscore a need for multi-level interventions to advance oral health equity.